Penerapan Optimasi Convolutional Neural Network untuk Klasifikasi Multi-Kelas Tumor Otak pada Citra MRI - Vina Ayumi (JSAI (Journal Scientific and Applied Informatics), 2026)
Brain tumors are among the most critical neurological diseases and require early and accurate diagnosis to support appropriate medical treatment. Magnetic Resonance Imaging (MRI) is widely used for brain tumor detection due to its high-resolution imaging capability; however, manual analysis of MRI images is time-consuming and highly dependent on the expertise of radiologists. Therefore, this study aims to apply an optimized Convolutional Neural Network (CNN) for multi-class brain tumor classification using MRI images. The dataset used in this study consists of 7,023 MRI images, categorized into four classes: glioma, meningioma, pituitary, and healthy, and divided into training, validation, and testing subsets. The research stages include image preprocessing, CNN architecture design, hyperparameter optimization, model training for 50 epochs, and performance evaluation. The training process achieved an accuracy of 87.44%, while the validation accuracy reached 85%, indicating good model generalization. Model evaluation on the test dataset using a confusion matrix, precision, recall, F1-score, and accuracy resulted in an overall accuracy of 77.8%.